Brand reallocation and market concentration - Jeremy Pearce; Liangjie Wu (Federal Reserve Bank of New York, 2024)
We study the interaction of customer capital and productivity through brand reallocation across firms. We develop a firm dynamics model with brands as transferable customer capital, heterogeneous firm productivity, and variable markups. We study the matching process between transferable brand capital and core productivity, which can be inefficient with significant welfare implications. We link USPTO trademark data with Nielsen sales data to study the prevalence of brand reallocation and the response of sales and prices to reallocation. Quantitatively, brand reallocation reduces welfare. Optimal policies deviate substantially from the literature due to the complementarity between brand capital and productivity.
Keywords: O31; O32; O34; O41; D22; D43; L11; L13; L22; 330; firm dynamics; productivity; market concentration; product innovation; reallocation; mergers & acquisitions; brands; trademarks; intangible assets